Re-engineering the Neo-Modernist Hermeneutics for the Post-Truth Digital Sphere - Atoillah, Muhammad Agil; Saryulis, Muhammad Irham (Yayasan Pesantren Mahasiswa An-Nur, 2025)
The intellectual legacy of Islamic Neo-Modernism, grounded in the hermeneutics of Fazlur Rahman and operationalized by Nurcholish Madjid and Abdurrahman Wahid, successfully transitioned Indonesia from authoritarianism to democracy by reconciling Islamic authenticity with pluralism. However, the efficacy of this